2018
DOI: 10.1002/brb3.938
|View full text |Cite
|
Sign up to set email alerts
|

The integration between nonsymbolic and symbolic numbers: Evidence from an EEG study

Abstract: IntroductionAdults can represent numerical information in nonsymbolic and symbolic formats and flexibly switch between the two. While some studies suggest a strong link between the two number representation systems (e.g., Piazza, Izard, Pinel, Le Bihan, & Dehaene, 2004 Neuron, 44(3), 547), other studies show evidence against the strong‐link hypothesis (e.g., Lyons, Ansari, & Beilock, 2012 Journal of Experimental Psychology: General, 141(4), 635). This inconsistency could arise from the relation between task de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 53 publications
2
27
3
Order By: Relevance
“…The discrepancies observed in the literature might be related to differences in the stimulus characteristics (e.g., number range and numerical correspondence between formats, see also Liu et al 23 , 24 ) and experimental tasks. Indeed, the majority of the studies showing evidence for format interdependence have employed explicit tasks (i.e., required participants to make an intentional numerical decision), while implicit measures are rarely used.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The discrepancies observed in the literature might be related to differences in the stimulus characteristics (e.g., number range and numerical correspondence between formats, see also Liu et al 23 , 24 ) and experimental tasks. Indeed, the majority of the studies showing evidence for format interdependence have employed explicit tasks (i.e., required participants to make an intentional numerical decision), while implicit measures are rarely used.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently making use of implicit paradigms (e.g., passive viewing) —where the numerical representation is probed per se, independently of any decisional strategies 20 , 25 , might be better suited to provide an objective (i.e., free of any intentional confounds) measure of the integration across numerical formats 26 – 28 . Two EEG studies used such implicit measures to examine the integration across numerical formats 23 , 29 . Their findings, however, are somewhat contradicting.…”
Section: Introductionmentioning
confidence: 99%
“…As in previous analyses, we compared the data from the Easy and the Hard trials of the Addition, with the identical trials of the Color-Group, in order to avoid that our P2p amplitude analyses were influenced by perceptual factors (e.g., Gebuis and Reynvoet, 2013 ; Liu et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…N1 and P2p would represent the early and late steps of the number-related processing. P2p is thought to arise from the recruitment of parietal networks involved in numerical processing (Piazza et al, 2004 ) and the increase of its amplitude would reveal the effort to discriminate between arrays of elements, which is a function of its ratio i.e., the Weber law, (Dehaene, 1996 ; Temple and Posner, 1998 ; Libertus et al, 2007 ; Liu et al, 2018 ). Some studies have reported that P2p amplitude is influenced by the evaluation of the perceptual visual features of dots arrays (e.g., Gebuis and Reynvoet, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that loading WM with visual-feature maintenance encoding, for example, by increasing the set size for a memory sample of colors, would increase the posterior P2 amplitude (Zhou and Thomas, 2015). It has also been reported that the posterior P2 is related to nonsymbolical numerical processing, with its amplitude increasing according to the effort necessary to discriminate between the numerical magnitude of arrays (Libertus et al, 2007;Hyde and Wood, 2011;Gouet et al, 2018;Liu et al, 2018). This is in agreement with evidence that the posterior P2 component is enhanced by high cognitive demands.…”
Section: Wm Load May Trigger Dynamic Adjustments In Cognitive Controlmentioning
confidence: 99%